2021
DOI: 10.3390/vision5040051
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 in Conjunctiva and Tears and Ocular Symptoms of Patients with COVID-19

Abstract: This study investigates the presence of SARS-CoV-2 in conjunctival secretions and tears and evaluates ocular symptoms in a group of patients with COVID-19. We included 56 hospitalized patients with COVID-19 in this cross-sectional cohort study. Conjunctival secretions and tears were collected using flocked swabs and Schirmer strips for SARS-CoV-2 reverse-transcriptase polymerase chain reaction (RT-PCR). Assessment of ocular surface manifestations included an OSDI (Ocular Surface Disease Index) questionnaire. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…Only a few studies in the literature comparing CT values in ocular and nasopharyngeal samples have been published. Ares et al, Karabela et al, and Gijs et al reported results similar to ours [ 18 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Only a few studies in the literature comparing CT values in ocular and nasopharyngeal samples have been published. Ares et al, Karabela et al, and Gijs et al reported results similar to ours [ 18 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 89%
“…Hany et al, Arora et al, and Kaya et al reported higher rates of 28.57%, 28%, and 16%, respectively, than found in our study [ 10 12 ]. In some other studies, a lower positivity rate, ranging from 0.8 to 7, was found [ 13 18 ]. This variability could have been due to multiple factors, such as differences in hygiene practices, race, timing of conjunctival swab, technique of conjunctival swab removal, patient compliance, or different virus subtypes in different geographical regions.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…SARS-CoV-2 prevalence in tears has already been explored in other studies, ranging from 0% to 57% [ 27 , 28 ]. Most of these studies used only CS for tear collection [ 27 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ], one study used only SS [ 43 ], and four other studies used both tear collecting methods [ 44 , 45 , 46 , 47 ]. Our study confirms previous findings that CS samples had a higher SARS-CoV-2 detection rate compared to SS samples, and the viral loads in tear samples were lower compared to nasopharyngeal samples [ 44 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies used only CS for tear collection [ 27 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ], one study used only SS [ 43 ], and four other studies used both tear collecting methods [ 44 , 45 , 46 , 47 ]. Our study confirms previous findings that CS samples had a higher SARS-CoV-2 detection rate compared to SS samples, and the viral loads in tear samples were lower compared to nasopharyngeal samples [ 44 , 45 , 46 , 47 ]. This is possibly because conjunctival scratching permits the collection of conjunctival cells, resulting in a larger volume of samples and, consequently, higher positivity rates.…”
Section: Discussionmentioning
confidence: 99%